Repetitive transcranial magnetic stimulation for psychiatric symptoms in long-term hospitalized veterans with schizophrenia: A randomized double-blind controlled trial - Su, Xiuru; Zhao, Long; Shang, Yujie; Chen, Yingnan; Liu, Xiaowen; Wang, Xuan; Xiu, Meihong; Yu, Huijing; Liu, Lijun (Frontiers in Psychiatry, 2022)
Multiple lines of evidence demonstrate that high-frequency (HF) repetitive transcranial magnetic stimulation (rTMS) may improve clinical outcomes in patients with schizophrenia (SCZ). However, the efficacy of HF-rTMS on psychiatric symptoms remains unknown in veterans with SCZ. This study aimed to investigate whether HF-rTMS was beneficial in alleviating the clinical symptoms in veterans with SCZ. Forty-seven long-term hospitalized veterans with SCZ were randomly allocated to receive neuronavigated 10 Hz rTMS or sham stimulation over the left dorsolateral prefrontal cortex once daily for four consecutive weeks. Symptoms were assessed by using the Positive and Negative Syndrome Scale at baseline and at the end of week 4. We also collected easily available routine biochemical markers including blood sugar, lipid profiles, hormone, and blood cell counts, considering that these markers may potentially be used to predict the outcomes of rTMS treatment. We found that there was a significant interaction effect of time and group on the positive symptoms. Compared with the sham group, the positive factor score of veterans with SCZ was significantly decreased after treatment in the real rTMS group. Interestingly, the improvement of positive symptoms from baseline to 4-week follow-up was significantly associated with the whole white blood cells (WBC) counts at baseline in the real rTMS group, and baseline WBC counts were predictive of the symptom improvement after rTMS treatment. Our findings indicate that add-on 10 Hz rTMS is beneficial for clinical symptoms in veterans with SCZ. In addition, the baseline WBC counts were predictive of the outcomes after treatment. Clinical trial registration clinicaltrials.gov, identifier NCT03774927.